2013
DOI: 10.1371/journal.pone.0057603
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sensitive Serum microRNA Biomarkers for Radiation Biodosimetry

Abstract: Exposure to ionizing radiation through environmental, occupational or a nuclear reactor accident such as the recent Fukushima Daiichi incident often results in major consequences to human health. The injury caused by radiation can manifest as acute radiation syndromes within weeks in organs with proliferating cells such as hematopoietic and gastrointestinal systems. Cancers, fibrosis and degenerative diseases are also reported in organs with differentiated cells, months or years later. Studies conducted on ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 43 publications
2
93
1
1
Order By: Relevance
“…It is very likely that after in vivo irradiation, the blood will contain other radiation-responsive miRNAs in exosomes. For example, Jacob et al (25) identified miR-150 as a sensitive biomarker of in vivo exposure in mouse serum.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very likely that after in vivo irradiation, the blood will contain other radiation-responsive miRNAs in exosomes. For example, Jacob et al (25) identified miR-150 as a sensitive biomarker of in vivo exposure in mouse serum.…”
Section: Figmentioning
confidence: 99%
“…This published finding inspired the search for other radiation-responsive miRNAs (19)(20)(21)(22). The radiation-induced miRNA response depends on radiation dose, time post exposure, genetic background (23)(24)(25)(26), the tissue being investigated and gender (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular miRNAs that can function in recipient cells are named as shuttle miRNAs, it may convey specific information from its donor cells to other recipient cells and hence plays various physiological functions. Recent studies have suggested that the expressions of specific miRNAs in blood plasma could be used as biomarkers of radiation dosimetry [17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…Frequency of occurrence of cells with dumbbell-shaped nuclei depends on the dose of irradiation and this correlation is described by a linearquadratic function with the following equation: y = 0.003+0.014x +0.005x 2 [31]. We would like to emphasize that the simplest biomarkers (nuclei abnormalities) we suggest for radiation exposure detection in vivo is not an alternative to classical radiation biomarkers in vitro [17], as well as to other modern approaches [2][3][4][5][44][45][46]. Detection of chromosomal aberrations (dicentrics) and the cytochalasine B micronucleus and "Cytome" methods are reliable bioindication and biodosimetry methods.…”
Section: Dumbbell-shaped Nucleimentioning
confidence: 99%